PENGARUH KOMPETENSI DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA SUB BAGIAN URUSAN DALAM SEKRETARIAT DAERAH PROVINSI JAWA BARAT - Giri Nugroho; Yogi Suprayogi Sugandi; Susniwati (Halu Oleo University, 2023)
The aim of this research is to find out how much influence simultaneously between Competency and Work Culture has on Employee Performance in the Internal Affairs Sub-Section of the Regional Secretariat of West Java Province. The population of this study were employees of the Internal Affairs Subdivision of the Regional Secretariat of West Java Province. The sample used in this study amounted to 63 respondents. The data analysis method used is descriptive quantitative and multiple linear regression analysis with SPSS tools. In this study data and information were collected from respondents using a questionnaire or questionnaire. The results of this research show that there is an influence of Competency on employee performance, there is no influence of work culture on employee performance, and there is an influence of Competency and Work Culture on Employee Performance in the Internal Affairs Sub-Section of the Regional Secretariat of West Java Province of 96.8%. This means that competency and work culture can explain variations in employee performance in the Internal Affairs Sub-Section of the Regional Secretariat of West Java Province by 96.8%.